Corporate Punishment - T. Riza Zarzani; Ismaidar; Br. Barus, Juita Novalia (PT. Sinergi Legal Publisher, 2024)
Alexander, K. (1999). Corporate criminal liability: Theory and Evidence. Cambridge University Press. Balaram Adhikari (2022). Corporate Criminal Law Reform in Indonesia. Jakarta: Student Library. This book provides an overview of corporate criminal law reform in Indonesia, with a focus on changes and new challenges. Bell, R. E. (2017). Companies behaving badly: Perspectives on corporate misconduct. Risky Business, 152-185. Burton, B. P. (Ed.). (2014). Corporate criminal liability: Federal law and prosecutorial discretion issues. Nova Science Publishers. Doyle, C. (2021). Corporate criminal liability: An overview of federal law. In Burton, BP (Ed.), Corporate criminal liability: Federal law and prosecutorial discretion issues (pp. 1-40). Nova Science Publishers. Farrell, N. (2011). Attributing criminal liability to corporate actors: Some lessons from the international tribunals. Journal of International Criminal Justice, 8(3), 731-755. Ginting, Sakeus. 2012. Corporate Punishment Policy for Laundering Crimes Money, Udayana University. HM Putra & Ahyani (2022). Criminal Liability for Corporate Crime in Indonesia. ResearchGate. This article explores the sources of corporate criminal responsibility in Indonesia, including the Criminal Code and the Limited Liability Company Law. Ministry of Law and Human Rights (2019). Article 46 Manuscript of the Draft Criminal Code Bill September 2019. Ministry of Law and Human Rights (2019). Article 48 Manuscript of the September 2019 Criminal Code Bill. Mahareksha S. Dillon (2022). Corporate Criminal Liability Under Indonesia's New Criminal Code. Conventus Law. This article discusses criminal sanctions for corporations according to the new Criminal Code, including fines and other additional sanctions​ (Conventus Law)​. Ratno Lukito (2020). Law and Development in Indonesia: Corporate Crime and Legal Framework. Springer. This book explains the relationship between legal development and corporate crime in Indonesia. Raganatha, BS 2017. Review of Criminal Liability for Perpetrating Corporations Insider Trading in the Capital Market. Legal Reflections: Journal of Legal Studies. Sudaryanto, et al. (2022). Corporate Criminal Responsibility in Indonesia. Jakarta: Rajagrafindo Persada. This book investigates the concept and practice of corporate criminal responsibility in Indonesia, including analysis of real cases. Suhartati, et al. 2014. Textbook of the Anatomy of Corporate Crime, Surabaya: PT. Revika Petra Media. Wibowo, Rizal Arya. 2020. Corporate Punishment.